Genetic Polymorphisms in FGFR2 Underlie Skeletal Malocclusion - Jiang, Q.; Mei, L.; Zou, Y.; Ding, Q.; Cannon, R.D.; Chen, H.; Li, H. (Journal of dental research, 2019)
Fibroblast growth factor receptor 2 (FGFR2) in craniofacial bones mediates osteoprogenitor proliferation, differentiation, and apoptosis. The distortion of proper craniofacial bone growth may cause class II and class III skeletal malocclusion and result in compromised function and aesthetics. Here, we investigated the association between variations in FGFR2 and skeletal malocclusions. First, 895 subjects were included in a 2-stage case-control study with independent populations (stage 1: n = 138 class I, 111 class II, and 81 class III; stage 2: n = 279 class I, 187 class II, and 99 class III). Eight candidate single-nucleotide polymorphisms (SNPs) in FGFR2 were screened and validated. Five SNPs (rs2162540, rs2981578, rs1078806, rs11200014, and rs10736303) were found to be associated with skeletal malocclusions (all P < 0.05). That is, rs2162540 was significantly associated with skeletal class II malocclusion, while others were associated with skeletal class III malocclusion. Electrophoretic mobility shift assay and chromatin immunoprecipitation analysis showed that the common genotypes of rs2981578 and rs10736303 contained the binding sites of RUNX2 and SMAD4. Compared with the common genotypes, the minor genotypes at these 2 SNPs decreased the binding affinity and enhancer effect of RUNX2 and SMAD4, as well the levels of FGFR2 expression. In addition, FGFR2 expression contributed positively to osteogenic differentiation in vitro. Thus, we identified FGFR2 as a skeletal malocclusion risk gene, and FGFR2 polymorphisms regulated its transcriptional expression and then osteogenic differentiation.